Association between detection of non-diabetic hyperglycaemia and vascular complications. (13th November 2019) - Palladino, R; Tabak, A G; Khunti, K; Valabhji, J; Majeed, A; Millett, C; Vamos, E P
Abstract: Background: The benefit of screening for non-diabetic hyperglycaemia (NDH) is still debated. Furthermore, the associated risk of vascular complications following a diagnosis of Type 2 diabetes (T2D) in people previously detected as NDH in real-world settings is not known. We examined the presence of vascular disease in newly diagnosed T2D individuals by glycaemic status within 3 years of diagnosis. Methods: We identified 159, 736 individuals diagnosed with T2D from the Clinical Practice Research Database in England between 2004 and 2017. We used logistic regression models to compare presence of microvascular (retinopathy and nephropathy) and macrovascular (coronary artery events, cerebrovascular and peripheral arterial disease) disease at the time of T2D diagnosis by prior glycaemic status. Models were adjusted for age, sex, ethnicity, deprivation, smoking status, blood pressure, cholesterol, and number of primary care visits. Results: There was a strong association between baseline glycaemic status and presence of microvascular complications at diabetes diagnosis (normoglycaemia 30.7%, no glycaemic test 36.7%, NDH 42.4%). Similarly, prevalence of macrovascular disease was lower for those with normoglycaemia(26.9%) compared with NDH(29.8%). Compared with individuals with normoglycaemia, those detected with NDH before the diagnosis of T2D had 76% and 53% increased odds of retinopathy and any microvascular complications (AOR 1.76, 95%CI 1.69-1.85; AOR 1.53, 95%CI 1.41-1.65), and 7% higher odds of diagnosis of acute coronary events (OR 1.07, 95%CI 1.03-1.12) at time of diagnosis of T2D. Conclusions: Microvascular and macrovascular diseases are detected in 40 and 20% of newly diagnosed T2D. NDH before the diagnosis of T2D was more likely associated with microvascular complications and acute coronary events. Detection of NDH might represent opportunities for reducing the burden of microvascular disease through heightened attention to screening for microvascular complications. Key messages: Detection of non-diabetic hyperglycaemia before the diagnosis of Type 2 diabetes was more likely associated with microvascular complications and acute coronary events. Detection of non-diabetic hyperglycaemia might represent opportunities for reducing the burden of microvascular disease through heightened attention to screening for microvascular complications.